1981
DOI: 10.1016/0045-6039(81)90024-5
|View full text |Cite
|
Sign up to set email alerts
|

Responses of normal and malignant cells to collagen, collagen-derived peptides and the C5-related tumor cell chemotactic peptide

Abstract: Two variant subpopulations of murine fibrosarcoma cells that differ significantly in their malignant potential and normal mouse fibroblasts were compared with regard to ability to respond chemotactically to collagen, collagen-derived peptides and the C5-derived tumor cell chemotactic peptide. Two distinct patterns of responsiveness were observed. The normal fibroblasts and non-metastasizing fibrosarcoma cells responded to the collagen products but not the C5 peptide. The metastasizing fibrosarcoma cells respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…It has been shown that collagen, a major component of most connective tissues (for review see Bornstein and Sage, 1980) and collagen-derived peptides are chemotactic for some tumor cells (Mundy et al, 1981). However, cells from a highly malignant fibrosarcoma cell line have been reported to lack chemotactic activity in response to collagen and collagen peptides, whereas cells from a nonmetastatic fibrosarcoma do respond as control cells (Wass et al, 1981). Cellular fibronectin, which is also present in connective tissues (for review see Hynes and Yamada, 1982) can therefore play a major role in recruitment of cells from certain tumors to connectivetissue-rich organs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that collagen, a major component of most connective tissues (for review see Bornstein and Sage, 1980) and collagen-derived peptides are chemotactic for some tumor cells (Mundy et al, 1981). However, cells from a highly malignant fibrosarcoma cell line have been reported to lack chemotactic activity in response to collagen and collagen peptides, whereas cells from a nonmetastatic fibrosarcoma do respond as control cells (Wass et al, 1981). Cellular fibronectin, which is also present in connective tissues (for review see Hynes and Yamada, 1982) can therefore play a major role in recruitment of cells from certain tumors to connectivetissue-rich organs.…”
Section: Discussionmentioning
confidence: 99%
“…The high malignant line responded to both of the chemotactic peptides and to TPA while the low malignant line was unresponsive. In this respect, the low This was not surprising because with regard to a number of other characteristics as well, the low malignant cells seem to be very similar to normal fibroblasts (17,24,(37)(38)(39). On the other hand, the rat peritoneal leukocytes and the two mylogenous cell lines did become hyperadherent when stimulated with TPA.…”
Section: Kinetics Of Stimulated Adherencementioning
confidence: 90%
“…Recent studies have shown that native collagen, intact ct collagen chains, and di and tri peptides derived from collagen are chemotactic for a variety of normal and malignant cell types. What is interesting is the fact that the spectrum of tumor cells which respond to the collagen peptides appears to be very similar to the spectrum of cells that respond to the bone factor (9,10,24). The nonmineral fraction of the bone matrix is, of course, nearly all collagen.…”
Section: Chemotactic Activation Of Tumor Cells In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…This is further supported by the observation that bone undergoing active resorption facilitated adhesion [12] and chemotaxis [13,14] of tumor cells to bone compared to non-resorbing bone. Collagen products appear to be one component of bone that induces tumor chemotaxis [15]. The factors through which bone induces chemotaxis are not clear.…”
Section: Chemotaxismentioning
confidence: 99%